Evaluating the Effectiveness of Educational Materials Used in Teaching English: Experiences and Insights from Teachers - Abdulhadi Masoud Aljadi (المجلة الليبية للدراسات الأكاديمية المعاصرة, 2025)
The objective of the study is to ascertain the resources employed for instructing English as a Foreign Language (EFL) reading and the challenges in selecting materials that address learners' requirements and capabilities. The objective is to evaluate’educators' perspectives on. English Language Teaching (ELT) materials used in reading sessions and the criteria employed in the selection or creation of these materials. This study employed a qualitative method. The data were gathered via pre-interviews, analysis of lesson plans, and post-interviews involving three English as a Foreign; Language (EFL) instructors from Libyan international schools. The data was examined with semantic analysis. The study revealed that the prevalent reading resources utilised by English as a Foreign Language (EFL)’ instructors were reading texts, quizzes, images, and music videos.; Research has demonstrated that the determinants affecting educators' perspectives on the selection of reading materials include; motivation, competency, interest, and topic matter. ; This study revealed that educators' perceptions of reading materials are significantly shaped by their teaching experience, student characteristics, and contextual elements. However, the participants noted that the limited professional development; and training impedes them in obtaining; enough abilities in teaching English as a Foreign Language;(EFL) reading and in selecting resources. This study elucidates and substantiates the criteria established by the respective ’educators in the selection or creation of reading materials. It would aid educators and education policy planners through insights on the demands of English as Foreign Language (EFL) teachers in strengthening their knowledge in materials selection.